2014
DOI: 10.1007/s10709-014-9801-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of yellow mosaic virus (YMV) resistance in soybean (Glycine max L. Merr.) through association mapping approach

Abstract: Yellow Mosaic Virus (YMV) is a serious disease of soybean. Resistance to YMV was mapped in 180 soybean genotypes through association mapping approach using 121 simple sequence repeats (SSR) and four resistance gene analogue (RGA)-based markers. The association mapping population (AMP) (96 genotypes) and confirmation population (CP) (84 genotypes) was tested for resistance to YMV at hot-spot consecutively for 3 years (2007-2009). The genotypes exhibited significant variability for YMV resistance (P < 0.01). Mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Since the initial cloning of SNCA , there have been multiple PD-related genes identified that additionally converge on the related autophagy-lysosome system and vesicle trafficking pathways (summarized in Table 1, extensively reviewed in [28, 32]). We will therefore summarize some of the key characteristics and players in these intracellular events before turning to the evidence that addresses the role(s) of LRRK2 in vesicle uptake and recycling.…”
Section: Genetic Clues For Altered Vesicular Dynamics In Pdmentioning
confidence: 99%
“…Since the initial cloning of SNCA , there have been multiple PD-related genes identified that additionally converge on the related autophagy-lysosome system and vesicle trafficking pathways (summarized in Table 1, extensively reviewed in [28, 32]). We will therefore summarize some of the key characteristics and players in these intracellular events before turning to the evidence that addresses the role(s) of LRRK2 in vesicle uptake and recycling.…”
Section: Genetic Clues For Altered Vesicular Dynamics In Pdmentioning
confidence: 99%
“…They indicated a Single Nucleotide Polymorphism (SNP) on chr 18 (LG G) with a possible association with MYMIV resistance gene. Kumar et al (2015) reported a region on chr 17 (LG D2) in significant linkage disequilibrium with resistance gene in association mapping study. But none of the reported linkage has been validated in mapping population.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, a single‐nucleotide polymorphism on chromosome 18 showed a possible association with a MYMIV resistance gene. Kumar et al (2015) found a region on chromosome 17 in significant linkage disequilibrium with MYMIV resistance in an association mapping study. Recently Rani et al (2017) mapped a MYMIV resistance gene on chromosome 6 very close to the two SSR markers Satt322 and GMAC7L.…”
Section: Discussionmentioning
confidence: 97%
“…In that study, a single-nucleotide polymorphism on chromosome 18 showed a possible association with a MYMIV resistance gene. Kumar et al (2015) found a region on chromosome 17 in significant linkage disequilibrium with MYMIV resistance in an association mapping study.…”
Section: Locusmentioning
confidence: 97%
See 1 more Smart Citation